Pengaruh Styrofoam Sebagai Bahan Tambah Pada Campuran Laston Lapis Aus - Naisel Lolok; Nur Ali; Rais Rachman (Paulus Civil Engineering Journal, 2021)
Styrofoam is waste from the disposal of electronic material buffers. This waste can be found in several main places in electronic store warehouses. This study aims to determine the value of the characteristics of the mixture of Laston Lapis Aus the effect of Styrofoam as an additive on the characteristics of the mixture of Laston Lapis Aus which uses the Malili river aggregate and Styrofoam as an added material through testing. The method used is the Conventional Marshall Method which tests and analyzes the characteristics of the mixture. The results showed the characteristics of the Laston Lapis Aus mixture using Malili River Stone and Styrofoam as added materials. Through Marshall test testing, the mixed characteristic values, namely stability, flow, VIM, VMA, and VFB all met the General Specifications of Highways 2018. The effect of adding Styrofoam to the mixture Laston Lapis Aus is able to fill voids in the mixture which makes the voids smaller, making the bonds between the aggregates stronger so that with the addition of Styrofoam the mixture becomes more water-resistant/resistant to water, weather and traffic loads.